PENDIDIKAN YANG MENINDAS (Tinjauan Kritis Terhadap Pendidikan di Indonesia) - SAPUTRA, ANDI (Universitas Islam Negeri Raden Intan Lampung, 2014)
Education is not only a means of transferring knowledge, social and culture, but also a means of inheriting ideology of the nation to the next generation. A nation becomes strong, courageous, and glorious, and conquers other nations by its strong and good educational system, and its implementation. It is generally believed that the education of a nation will automatically follow the ideology of that nation. Pancasila as the ideology of Indonesian should properly become spiritual aspect of national education system. Ironically, it remains a history which was shouted so often to ease the oppressors’ existence in a covered oppression. Besides, it seems that nowadays educational philosophy has lost its identity due to consuming western educational philosophy superfluously. In this case, it is imperative that education in Indonesia should return to our national philosophy, Pancasila, for the sake of prestige and identity of the nation